Analysis of Fatty Acid Profiles of Pistachios (Pistacia vera L.) and Native Walnuts (Juglans regia L.) from Turkey - DOGAN, ADNAN; ÇELIK*, FERIT; BALTA†, FIKRI; JAVIDIPOUR‡, I.; YAVIC§, ADNAN (Asian Journal of Chemistry, 2009)
This work identifies fatty acid compositions of 7 pistachio varieties (Pistacia vera L.) from G. Antep and Siirt (southeastern Turkey) and 9 walnut (Juglans regia L.) genotypes from Denizli (western Turkey). Pistachio varieties contained 57.77 % oil, 8.73 % palmitic acid, 0.81 palmitoleic acid, 2.26 % stearic acid, 71.90 % oleic acid, 14.91 % linoleic acid, 0.88 % linolenic acid, 0.08 % myristic acid, 0.11 % arachidic acid and 0.21 % gadoleic acid, respectively. Walnut genotypes contained 65.57 % oil, 5.80 % palmitic acid, 0.16 palmitoleic acid, 2.65 % stearic acid, 59.85 % oleic acid, 14.20 % linoleic acid, 0.88 % linolenic acid, 0.08 % myristic acid, 0.11 % arachidic acid and 0.21 % gadoleic acid, respectively. The mean ratio of unsaturated fatty acids and saturated fatty acids was 8.02 for pistachio varieties and 11.0 for walnut genotypes.